Developing and piloting a framework for studying the alignment of mathematics examinations with the curriculum - Osta, Iman (2016)
This research aimed at developing a methodological framework to investigate the alignment of the Lebanese national math exam tests with the curriculum at the middle school level, during the transitory period of a major curricular reform. The focus is on exploring the characteristics of an “assessment culture” set by the national exams during the long life of the old curriculum.